Performance, carcass and organ weight characteristics of broiler chickens fed diets containing graded levels of Gongronema latifolia - Ukorebi, B. A; Akpet, S. O (Nigerian Journal of Animal Science, 2023)
A forty-nine day (7 weeks) feeding trial was conducted on 150 day-old Anak 2000 broiler chicks to evaluate the effect of graded levels of Gongronema latifolia leaf meal on the performance, carcass/organ weight characteristics in a completely randomized design. The birds were assigned to five dietary treatments of 30 birds each, subdivided into 3 replicates, each containing 10 birds. There were no significant (P>0.05) treatment effects in average initial weights, average final body weight, average body weight gain and feed conversion ratio. There was significant depression in average daily feed intake (P<0.05) at 10% dietary level. Dietary levels of 2.5%, 5.0% and 7.5% GLLM (P<0.05) increased dressing percentage of the experimental birds. Percentage weights of necks, wings, thighs, drum sticks, breasts, hearts, liver, spleen, lungs and pancreas (expressed as percentage of live weights) were similar (P>0.05). However, dietary levels of 2.5% - 10.0% GLLM yielded significantly higher (P<0.05) percentage weights of proventriculus than the control diet. The result obtained from the experiment suggests that 7.5% dietary inclusion of the leaf meal can support normal broiler production.